2013
DOI: 10.1021/jo401476f
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed α-Arylation of Zinc Enolates of Esters: Reaction Conditions and Substrate Scope

Abstract: The intermolecular α-arylation of esters by palladium-catalyzed coupling of aryl bromides with zinc enolates of esters is reported. Reactions of three different types of zinc enolates have been developed. α-Arylation of esters occurs in high yields with isolated Reformatsky reagents, with Reformatsky reagents generated from α-bromo esters and activated zinc, and with zinc enolates generated by quenching lithium enolates of esters with zinc chloride. The use of zinc enolates, instead of alkali metal enolates, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 87 publications
2
32
0
1
Order By: Relevance
“…[6] Ester zinc enolates generated in situ, which are known as Reformatsky reagents, [7] have also proven their utility in organic synthesis, including in Pd-catalyzed arylations. [8] However,the extensive application of Reformatsky reagents in synthesis has been hampered by the moderate air and moisture stability of these zinc enolates.W er ecently reported that the presence of Mg(OPiv) 2 (OPiv = OCOtBu) strongly enhanced the thermal, air,and moisture stability of solid aryl, benzyl, heteroaryl, and allyl zinc reagents. [9] These organometallic reagents containing magnesium and lithium salts were abbreviated for the sake of simplicity as RZnOPiv and referred to as organozinc pivalates,keeping in mind that the pivalate anion may also be coordinated to magnesium and/or lithium.…”
mentioning
confidence: 99%
“…[6] Ester zinc enolates generated in situ, which are known as Reformatsky reagents, [7] have also proven their utility in organic synthesis, including in Pd-catalyzed arylations. [8] However,the extensive application of Reformatsky reagents in synthesis has been hampered by the moderate air and moisture stability of these zinc enolates.W er ecently reported that the presence of Mg(OPiv) 2 (OPiv = OCOtBu) strongly enhanced the thermal, air,and moisture stability of solid aryl, benzyl, heteroaryl, and allyl zinc reagents. [9] These organometallic reagents containing magnesium and lithium salts were abbreviated for the sake of simplicity as RZnOPiv and referred to as organozinc pivalates,keeping in mind that the pivalate anion may also be coordinated to magnesium and/or lithium.…”
mentioning
confidence: 99%
“…28 These are common reagents used for Reformatsky reactions, and they can be generated from reactions of a-halo esters with zinc metal or by quenching the alkali metal enolates of esters with zinc halides. The first study was conducted with the isolated Reformatsky reagent from tert-butyl acetate or tert-butyl propionate in the presence of a catalyst (Scheme 13).…”
Section: Arylations Of Estersmentioning
confidence: 99%
“…Substrates bearing nitro, cyano, carboxy, and keto groups failed to react under these reaction conditions. Very recently, Hartwig and coworkers [110] present a full account of the scope and limitation of a mild and more general palladium-catalyzed coupling of zinc enolates of esters that were generated in situ from α-bromoesters or by quenching the alkali metal ester enolates. Aryl bromides as coupling partners were used along with [Pd(dba) 2 ]/QPhos or the palladium(I) dimer [P(tBu) 3 ]PdBr 2 .…”
Section: [D][e]mentioning
confidence: 99%
“…To overcome such complications, Hartwig and coworkers [109] developed an α-arylation reaction of esters under less basic conditions, which paralleled the cross-coupling reactions of zinc enolates. These coupling reactions, conducted with palladium catalysts bearing hindered monophosphane ligands, allowed that zinc enolates of esters (isolated Reformatsky reagents, zinc enolates generated in situ by reactions of α-bromoesters with Rieke's activated zinc or the related, but not identical, zinc enolate generated in situ by quenching the alkali metal enolates with ZnCl 2 ) underwent fast oxidative addition of aryl bromides at room temperature (Scheme 8.62) [110]. This significantly expanded the substrate scope and notably most of the reactions could be carried out at room temperature with no formation of diarylated products (Scheme 8.61) [109].…”
Section: [D][e]mentioning
confidence: 99%